Positive social relationships in hunting groups are related to compliance with the higher-level moose management - Tuominen, Laura S.; Wikström, Mikael; Helanterä, Heikki; Karell, Patrik; Rapeli, Lauri; Vuorisalo, Timo; Brommer, Jon E. (Resilience Alliance Publications, 2026)
Managing shared natural resources, such as moose (Alces alces) in Finland, is often challenging due to the involvement of multiple stakeholders with opposing views and the need for coordination across several spatial levels. A sustainable moose population is maintained through a carefully planned, multi-level system of adaptive management. However, ensuring that these plans are followed requires substantial support from the lowest level—the hunters. We investigated the decision-making and joint action of moose hunting groups, and how these are related to compliance with hunting recommendations. We conducted a country-wide questionnaire study with a sample of 4729 hunters in Finland. We applied the multidisciplinary social-ecological systems framework—rooted in systems thinking—alongside insights from evolutionary theory on cooperation. Our results showed that hunters who positively assessed social interactions and decision-making within their hunting group were more likely to be satisfied with and compliant toward natural resource management. To achieve long-term sustainability, we suggest that harvest regulations and recommendations should be accompanied by attention to the decision-making and group dynamics of those carrying out the harvest. We found that processes such as trust and frequent meetings that promoted social capital and communication within hunting groups, between groups, and between hunters and the national management level were crucial for sustainable local moose management. A balance between member commitment to the group and the regular acceptance of new members had a positive influence. Our results highlight that deeper understanding of local social dynamics can facilitate regional and national management of shared resources.